The mechanism of switching direction of swirling sloshing waves. (10th January 2023) - Chen, Bang-Fuh; Wu, Chih-Hua; Faltinsen, Odd Magnus
Abstract: Abstract : Swirling waves frequently occur in a three-dimensional tank under a nearly resonant excitation with oblique excitation angle. The oblique excitation produces two excitation components and the secondary component triggers rotational waves. The detailed mechanism of the switch in circular direction is clearly described in this study. The evolution of the hydrodynamic forces ( Fz ) on the tank walls presents a beating phenomenon and the switch direction always occurs at the peak and trough of the envelope of the Fz history. The external excitation moment changes the circulation intensity, and finally the swirling wave becomes a single-direction wave, but only for a short time. The profile of the single-direction wave was determined by the dominant sloshing mode and the instantaneous tank motion was found to be a key factor to determine the consequent swirling flow circulating direction.